2021
DOI: 10.1007/s00167-021-06463-5
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes were similar between hybrid and cemented TKAs performed on paired knees at a minimum 15 years of follow-up

Abstract: PurposeTo compare long‐term clinical and radiographic results and survival rates between hybrid and cemented total knee arthroplasties (TKAs) performed on paired knees. MethodsSeventy‐two patients with hybrid and cemented TKAs performed on paired knees with NexGen® cruciate‐retaining prostheses were retrospectively reviewed after a minimum 15 years of follow‐up. Mean follow‐up period was 17.5 years. Preoperative alignment deformity and range of motion (ROM) were not different between groups. The Knee Society s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 27 publications
(49 reference statements)
1
5
0
Order By: Relevance
“…Second, a hybrid cementation was performed which could lead to potentially worse radiological results. However, recent studies found similar results between hybrid and full cementation TKA at long-term follow-up [4,35]. Furthermore, all tibial components were cemented, and loosening was always observed on the tibial component in the present study.…”
Section: Discussionsupporting
confidence: 78%
“…Second, a hybrid cementation was performed which could lead to potentially worse radiological results. However, recent studies found similar results between hybrid and full cementation TKA at long-term follow-up [4,35]. Furthermore, all tibial components were cemented, and loosening was always observed on the tibial component in the present study.…”
Section: Discussionsupporting
confidence: 78%
“…Secondary exchange arthroplasty was performed following a diagnosis of aseptic failure based on clinical symptoms (including pain and swelling) and conventional radiographic criteria, defined as a progressive radiolucent line of ≥ 2‐mm width at the bone‐cement or bone‐implant interface, a significant change in component positions including subsidence, or a visible fracture of the surrounding cement [24]. A radiolucent line was defined as a radiolucent zone at the bone–cement or bone–implant surface parallel to the implant surface [29]. The location of the significantly progressive radiolucent lines was evaluated with reference to the zones suggested by the Knee Society radiographic evaluation method [29].…”
Section: Methodsmentioning
confidence: 99%
“…A radiolucent line was defined as a radiolucent zone at the bone–cement or bone–implant surface parallel to the implant surface [29]. The location of the significantly progressive radiolucent lines was evaluated with reference to the zones suggested by the Knee Society radiographic evaluation method [29].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total knee arthroplasty (TKA) is a useful treatment for patients with end-stage knee joint arthritis, and its long-term survivorship is reported to reach ≥90% 1,2 . However, despite its successful clinical outcomes, some patients experience complications and need to undergo revision surgery.…”
mentioning
confidence: 99%